(untitled) - Marti, Jed (Singapore, 1993)
The RLISP '88 programming system introduces an evolutionary approach to software development that enables small groups of programmers to advance the state of the art over a period of many years. Each new system is built on top of the old, yet little remains of the original program code. This book presents a style of durable programming for domain specialists and computer scientists alike. Exercises at the end of each chapter encourage its use as a textbook.
Keywords: LISP (Computer program language),Programming languages (Electronic computers)